ISLAMIC WORK ETHICS IN IMPROVING HR PERFORMANCE THROUGH COMMITMENT AFFECTIVE - Ulfa, Adilla Kustya; Riyanto, Fery (Universitas Dian Nuswantoro, 2023)
This study assesses a methodology for improving HR performance using affective Commitment and Islamic work ethics as modifying factors. 59 instructors who have taught at Islamic-based schools in Kawedanan Boja for more than five years responded to the questionnaire, providing the data for this study. Then, to estimate the causal association between variables, this data-gathering technique employs path analysis, which is an extension of multiple regression or regression analysis. The findings of this study suggest that the Islamic work ethic directly improves HR performance. Using affective Commitment as an intervention variable, the Islamic work ethic also positively affects HR performance since the stronger the Islamic work ethic, the higher the affective Commitment, which affects HR performance. Keywords: HR performance, Islamic work ethics, affective Commitment